Factors influencing free and open-source software adoption in developing countries—An empirical study - Silva, D.; Coutinho, C.; Costa, C. (Journal of Open Innovation: Technology, Market, and Complexity, 2023)
Free Open-Source Software (FOSS) is essentially seen by many organizations as a key pillar for accelerating technological innovation. This study aims to evaluate the extent to which factors such as cost and quality of the system, as well as usability, interoperability, and security, influence the intention to use FOSS. Based on the data obtained from the survey, we propose a new theoretical model that we test and evaluate using the SEM-PLS method. The results suggest a significant relationship between FOSS adoption and factors such as low cost, performance expectation, social influence, and system quality, which was explained on a large scale by safety, interoperability, and usability as the most important factors in adoption decisions. Thus, this paper presents a new model for the adoption of FOSS in countries with high growth potential and aims to be a significant contribution to the scientific community on the state of the art in FOSS organizations in developing countries.